Starving the enemy: how plant and microbe compete for sugar on the border - Chen, Jingsheng; Sun, Miao; Xiao, Guosheng; Shi, Rujie; Zhao, Chanjuan; Zhang, Qianqian; Yang, Shuo; Xuan, Yuanhu (Frontiers in Plant Science, 2023)
As the primary energy source for a plant host and microbe to sustain life, sugar is generally exported by Sugars Will Eventually be Exported Transporters (SWEETs) to the host extracellular spaces or the apoplast. There, the host and microbes compete for hexose, sucrose, and other important nutrients. The host and microbial monosaccharide transporters (MSTs) and sucrose transporters (SUTs) play a key role in the “evolutionary arms race”. The result of this competition hinges on the proportion of sugar distribution between the host and microbes. In some plants (such as Arabidopsis, corn, and rice) and their interacting pathogens, the key transporters responsible for sugar competition have been identified. However, the regulatory mechanisms of sugar transporters, especially in the microbes require further investigation. Here, the key transporters that are responsible for the sugar competition in the host and pathogen have been identified and the regulatory mechanisms of the sugar transport have been briefly analyzed. These data are of great significance to the increase of the sugar distribution in plants for improvement in the yield.